THE ROLE OF THE VILLAGE HEAD AS A MOTIVATOR IN IMPROVING THE WORKING DISCIPLINE OF APPARATUS AT THE PAMARANGAN KIWA VILLAGE OFFICE, TANJUNG SUB-DISTRICT, TABALONG REGENCY - Ahmad Rifa'i; Heni Suparti (JAPB, 2023)
Based on Law Number 6 of 2014, the village administration is the organizer of government affairs and regulates and manages the interests of the local community based on local origins and customs that have been recognized and respected by the community in the Indonesian government system. A village is usually formed from the merger of several villages or parts of adjoining villages, or it could be the expansion of a village into two or more villages, which are usually formed independently outside the existing village. Village government is one of the most important aspects of governance because the village is the subject of policy implementation. The village head, as one of the elements of the state apparatus in leading state government institutions or the bureaucracy at the village level, has an important role in the progress of a village, so in carrying out his daily duties related to presenting the required data and information, hard work and skills are increasingly required. optimally in order to expedite the implementation of government tasks, especially the work discipline of village officials who are entrusted with tasks in the field of administration and who occupy a strategic position as an organ of the village government and who know for sure all the conditions and problems that exist in the village. The purpose of this study was to find out and analyze the role of the village head as a motivator in improving the work discipline of Pamarangan Kiwa Village officials in Tanjung Sub-district, Tabalong Regency. This study uses a type of qualitative descriptive approach; the collection technique uses interviews with five key informants; and the data analysis techniques use an interactive model. The results of this study indicate that the role of the village head as a motivator in improving the work discipline of Pamarangan Kiwa Village officials, Tanjung sub-district, Tabalong Regency, is categorized as having a role. Keywords: role, motivator, work discipline